HUBUNGAN PERSEPSI PENDERITA TB PARU TENTANG PENCEGAHAN PENULARAN DENGAN UPAYA PENCEGAHAN PENULARAN TB PARU - Binarti Dwi Wahyuningsih (Bahasa Indonesia, 2016)
Pulmonary TB patients often do not have the habit of closing the mouth when coughing, it certainly can make the transmission of pulmonary TB in healthy persons in the vicinity. This study aims to analyze the relationship of pulmonary TB patient perceptions about prevention of transmission of pulmonary tuberculosis with pulmonary TB prevention efforts. The design used in this study is an analytic correlation with cross sectional. This study uses total sampling so that the sample is 22 respondents. Independent variable in this study is the perception of pulmonary tuberculosis patients on prevention of transmission and the dependent variable is the prevention of pulmonary TB transmission. Data were collected using a questionnaire and analyzed using cross tabulation. The results showed the majority of respondents had a negative perception take steps to prevent transmission of pulmonary tuberculosis with unfavorable by 10 respondents (83.3%). Results of cross-tabulation showed there is a relationship between the perception of pulmonary tuberculosis patients on prevention of transmission to the prevention of pulmonary TB transmission. The more positive perception of the better prevention was done, and vice versa. In order for pulmonary tuberculosis prevention efforts well underway, much needed positive perception about the prevention of pulmonary TB transmission.